Peran Pengemudi Bus PT Lion Group dalam Meningkatkan Layanan Ground Handling di Area Airside Bandara Internasional Hang Nadim Batam - Arfiandi Yudha; Elisabeth Endang Prakosawati (Jurnal Manajemen Bisnis Digital Terkini, 2025)
Hang Nadim International Airport in Batam is a growing air transportation hub, driven by increasing public mobility and aviation activity. Ground handling services in the airside area are crucial, particularly for buses transporting passengers to and from aircraft. However, several issues persist, such as late pick-ups, unsafe bus conditions, and frequent technical disruptions. This study aims to identify the role of PT Lion Group bus drivers in supporting ground handling services and analyze the impact of bus breakdowns on driver performance at the airport. The method used was descriptive qualitative, using observation, interviews, and documentation. Interviews were conducted with drivers, technicians, and Apron Movement Control (AMC) officers to obtain data on technical challenges and operational coordination. Observations were conducted during On-the-Job Training (OJT), and documentation was used to support the validity of the data. The results indicate that bus drivers play a crucial role in ensuring smooth ground handling services, but are frequently hampered by technical breakdowns, such as engine and braking system problems, which impact passenger comfort and On-Time Performance (OTP). Recommendations include improving bus maintenance, providing a backup fleet, and providing technical training for drivers to improve service effectiveness.